Lacunas no financiamento da saúde significam riscos crescentes para uma recuperação global - Kurowski, Christoph; Evans, David; Tandon, Ajay; Eozenou, Patrick; Schmidt, Martin; Irwin, Alexander; Postolovska, Iryna; Araujo, Edson (Jornal Brasileiro de Economia da Saúde, 2022)
Artigo de opinião